Singlet oxygen phosphorescence detection in vivo identifies PDT-induced anoxia in solid tumors. Issue 6 (17th April 2019) - Hackbarth, Steffen; Islam, Waliul; Fang, Jun; Šubr, Vladimír; Röder, Beate; Etrych, Tomáš; Maeda, Hiroshi
Abstract : Extracorporeal measurements through the skin achieve sufficient SNR to analyze 1 O2 kinetics and evaluate PDT efficiency. Abstract : Real-time surveillance of photodynamic therapy (PDT) has been desired by the research community for a long time. The impact of the treatment is encoded in the phosphorescence kinetics of its main mediator: singlet oxygen. We report successful in vivo measurements of these weak kinetics through the skin of living mice after systemic drug application. Using special high transmission optics centered around 1200, 1270 and 1340 nm, singlet oxygen phosphorescence can be clearly discriminated from other signals. N -(2-Hydroxypropyl)methacrylamide copolymers conjugated with pyropheophorbide-a exhibit highly selective accumulation in tumors. Signals of this drug in tumors were compared to those in normal tissue. In both places, the major part of the signal could be identified as arising from drug still circulating in the bloodstream. Despite high concentrations of extravasated drug in the tumors due to the EPR effect, nearly no signal could be detected from these photosensitizers in vivo, contradicting in vitro experiments. We propose that the reason for this discrepancy is oxygen depletion in tumor tissue in vivo, even at moderate (at PDT scale) illumination intensities, soon after the start of the illumination. These results underline the importance of singlet oxygen surveillance during PDT treatment.